(untitled) (Eurasian Journal of Philology Science and Education, 2026)
The article examines the functioning of medical texts in the so-called “alien” discourse, that is, in literary works, the language of mass media, and various talk shows. The aim of the study is to identify the specific features of representing medical knowledge related to human health, disease, and disease prevention in texts that do not belong to specialized medical discourse. Studying a medical text in “alien” discourse makes it possible to understand how language conveys the specific features of a doctor’s professional way of thinking, how medical consciousness is reflected, and how processes of producing and interpreting medical information are realized in non-specialized texts. In this study, “alien” discourse refers to non-specialized texts containing medical information and functioning in literary discourse, media language, and talk shows. The research employed content analysis and discourse analysis. The findings show that the active use of medical terminology emphasizes the objectivity of specialized information presented in the text while also exerting an implicit influence on the reader. The analysis of specialized, literary, and media texts related to human health revealed a shift in language register. The functioning of medical terms in “alien” discourse demonstrates their educational function. A specialized text contributes to the formation of a scientific worldview not only for doctors, but also for non-specialists. Texts of this type are marked by specific lexical units that characterize aspects of the professional worldview. Keywords: text, medical text, discourse, alien discourse, artistic discourse.